Simvastatin Improves Renal Function and Glomerulosclerosis in Ischemic-reperfusion Injury - Putu Nita Cahyawati; Desak Putu Oki Lestari; Ayu Savitri Siskayani; I Made Toya Ariawan (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Statin is an anti-cholesterol drug that is widely prescribed throughout the world. Statins are mainly used to treat and prevent cardiovascular disease. Several studies have found the pleiotropic effect of statin. However, related effect of statin in kidney failure is still unclear. Ischemic-reperfusion (I/R) injury is a major cause of acute kidney failure. This study aims to determine the effect of simvastatin on kidney function and glomerular conditions by periodic acid-schiff staining in I/R injury.METHODS: Eighteen male Swiss mice were grouped into sham operation group (GSO), I/R injury group (GIRI), and simvastatin group (GSIM). The GSO group was performed by sham operation and pretreatment of 1% carboxymethylcellulose (CMC) for 3 days. The GIRI group was performed by I/R procedure and pretreatment of 1% CMC for 3 days and the GSIM group was performed by I/R procedure and pretreatment of 10 mg/kg BW simvastatin for 3 days. Blood urea nitrogen (BUN) and creatinine serum were assessed to determine kidney function. Histopathological analysis of glomerulosclerosis was assessed by the extent of glomerular damage (sclerosis), capillary loops, and synechia. The data were analyzed by one-way ANOVA followed by post hoc Tukey’s test (p<0.05).RESULTS: The creatinine and BUN levels in the GIRI group were the highest (0.97±0.48) compared with the other groups. The glomerulosclerosis index in the GSO group was 0.75±0.56, the GIRI group was 3.55±0.61, and the GSIM group was 2.08±1.37. There was a significant difference in the glomerulosclerosis index between the GSO and GIRI groups, but there was no significant difference between the GIRI and GSIM groups. These differences include the formation of sclerosis in the glomerulus, capillary loop, and synechiae.CONCLUSION: Simvastatin improves kidney function and glomerulosclerosis in I/R injury.KEYWORDS: ischemic-reperfusion injury, simvastatin, glomerulosclerosis